'It's not doable!' Exploring physical education teachers' perspectives on the policy change of sport and physical education in Chinese universities. Issue 3 (3rd July 2017) - Chen, Xuedong; Chen, Shushu
ABSTRACT: In China, a decline in adolescents' physical fitness plus increased risks of chronic disease and obesity have led to recent policy changes in sport and physical education (PE) within the contexts of schools and universities. Although there has been increased research interest in issues related to youth sport and school sport, few studies focus on the university context. There is remarkably little bottom-up study examining how universities react to macro level policies in particular. Using case-study approaches, our research aims to explore PE teachers' perceptions regarding the roles of sport and the fitness test programme for university students along with these staff members' reactions to and perspectives on recent national policy changes. Guided by a theoretical framework for education policy analysis, the empirical section of this paper uses a series of interviews conducted with a range of senior sport staff members and PE teachers from the sport departments of four case-study universities in Tianjin, China. The paper reveals that the role and value of sport has indeed been upgraded against the background of a serious policy change at the national level; but variations are also apparent in the implementation of the policies at university level, with these variations affected by individual interests and perspectives and by universities' contextual constraints. The paper ends with an analysis of the implications associated with micro level policy analysis for university sport development in China.